Structural modification of swai-fish (Pangasius hypophthalmus)-based emulsions containing non-meat protein additives by ultra-high pressure and thermal treatments - Jiranat Techarang (2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group. Swai-fish emulsions containing fermented soybeans (thua nao and rice-koji miso) were pressurized at 600 MPa for 20 min or heated at 72°C for 30 min. The fish batters were blended with soy protein isolate (SPI) or whey protein concentrate (WPC) to stabilize the emulsions. The processed fish emulsions were then subjected to physical, chemical and microbiological examinations. The results of gel strength and water-holding potential showed that SPI addition yielded higher impact on these properties than WPC addition, which was also confirmed by the interactions between SPI and native fish proteins depicted by electrophoregrams. The frequency profiles suggested that the heated gels had a greater storage and loss moduli than pressurized gels, while pressurized WPC set-gel displayed larger loss tangent (the predominance of viscous moiety) than those pressurized SPI set-gel. High bacteria and spore counts of B. subtilis (residual of the thua nao) were observed in both pressurized and heated fish-based emulsions.